Liquid exfoliation of stanene as degradable nanoagents for NIR-II photothermal therapy. (10th June 2023) - Li, Xueqiao; Li, Weijian; Miao, Zhaohua; Lu, Chenxi; Ma, Hongna; Xu, Yan; Gong, Deyan; Xu, Cheng-Yan; Zha, Zhengbao
Highlights: A joint computational simulation and proof-of-concept experiment revealed that the degradation of newly-discovered stanene in oxygenated water environment was a water-accelerated oxidation process. Several protective strategies like alcohols were proposed to avoid or decrease the oxidation of stanene to maintain its inherent performance for further biomedical applications. Stanene was explored as second near-infrared (NIR-II) photonic agents for ablation of 4T1 tumor with a tumor-growth inhibition ratio up to 96.7%. The biodistribution, biodegradation and toxicity experiments demonstrated that stanene was suitable for biomedical applications. Abstract: Stanene, the two-dimensional form of elemental tin (Sn), is easily oxidized in the ambient environment, significantly hindering its applications in biomedical fields. However, the degradation mechanism of stanene remains unclear. Herein, combined DFT calculations and proof-of-concept experiments were conducted to elucidate the underlying degradation mechanism of stanene. The results reveal that the degradation of stanene in an oxygenated water environment is a water-accelerated oxidation process. H2 O molecules could not only facilitate the electron transfer from stanene to O2 because of the polarization effect of H2 O, but also directly react with the defect sites of stanene due to enhanced absorption energy. Moreover, several protective strategies like alcohol protection were proposed to avoid or mitigate the oxidation of stanene for further applications. Finally, stanene was explored as the second near-infrared (NIR-II) photonic agents for ablation of 4T1 tumor, depicting a tumor-growth inhibition ratio up to 96.7%, much better than that of the first near-infrared (NIR-I) group (65.5%). This work reveals the degradation mechanism of stanene and demonstrates its biomedical applications in the NIR-II region.